2013
DOI: 10.1007/s13524-013-0210-8
|View full text |Cite
|
Sign up to set email alerts
|

A “Mulatto Escape Hatch” in the United States? Examining Evidence of Racial and Social Mobility During the Jim Crow Era

Abstract: Racial distinctions in the United States have long been characterized as uniquely rigid and governed by strict rules of descent, particularly along the black-white boundary. This is often contrasted with countries, such as Brazil, that recognize "mixed" or intermediate racial categories and allow for more fluidity or ambiguity in racial classification. Recently released longitudinal data from the IPUMS Linked Representative Samples, and the brief inclusion of a "mulatto" category in the U.S. Census, allow us t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 26 publications
1
50
0
1
Order By: Relevance
“…There was some response churning between single-race white and single-race black responses (as found in historical data by Saperstein and Gullickson (2013) and Loveman and Muniz (2007)). …”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…There was some response churning between single-race white and single-race black responses (as found in historical data by Saperstein and Gullickson (2013) and Loveman and Muniz (2007)). …”
Section: Resultsmentioning
confidence: 73%
“…Using the limited data available, other scholars have raised important questions and given helpful insights (e.g., DeFina and Hannon 2016; Guo et al 2014; Harris and Sim 2002; Liebler and Ortyl 2014; Loveman and Muniz 2007; Saperstein and Gullickson 2013; Saperstein and Penner 2012, 2014). Previous empirical studies have been constrained in their ability to give information about all types of people in the United States.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Para este análisis también incorporamos dentro de este grupo a los individuos que se autoidentificaron como palenqueros y raizales. Aquellas personas que se identificaron como mulatas no fueron agregadas a esta categoría debido a que la literatura sobre el blanqueamiento aborda el concepto de la ventana de escape del mulato para dar cuenta de la existencia de un estatus intermedio entre personas blancas y negras en países como Brasil (Degler 1986), Colombia (Wade 1993) y los Estados Unidos (Saperstein y Gullickson 2013). Nos interesa analizar especialmente el rol de las categorías intermedias de autoreconocimiento étnico-racial (mulata y mestiza) en un contexto en el que ha primado la ideología del mestizaje.…”
Section: Variables Explicativasunclassified
“…It has also been observed that colorism, a system of racial stratification and social privilege that favors light complexion over dark complexion, plays a central role in defining standards of beauty for African Americans (hereafter blacks) (Harvey et al 2005;Maddox and Gray 2002;Thompson and Keith 2001). Numerous studies have shown the many ways in which colorism affects the African American community (Hannon et al 2013;Hochschild and Weaver 2007;Saperstein and Gullickson 2013;Ryabov 2013).…”
Section: Introductionmentioning
confidence: 99%